2021
DOI: 10.5603/fm.a2020.0101
|View full text |Cite
|
Sign up to set email alerts
|

A bifurcated plantaris muscle: another confirmation of its high morphological variability? Another type of plantaris muscle

Abstract: The plantaris muscle usually begins with a short, narrow belly in the popliteal fossa at the lateral supracondylar line of the femur and the knee joint capsule. Then it form a long and slender tendon and usually inserts into the calcaneal tuberosity on the medial side of Achilles tendon. Nevertheless, many anatomical variations of distal attachment have been described. Cases of atypical proximal origin are reported less frequently. In this paper, we have presented a case of a two headed plantaris muscle. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Olewnik et al [10] identi ed a "double PM" and a "bifurcated PM" in 0.8% of their sample, per each form. During a forensic autopsy, Smedra et al [14] observed a PM with two muscular heads that fused to a common tendon, which corresponds to Olewnik et al [10] "bifurcated PM". Futa et al [3] observed another morphological variant similar to Smedra et al [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Olewnik et al [10] identi ed a "double PM" and a "bifurcated PM" in 0.8% of their sample, per each form. During a forensic autopsy, Smedra et al [14] observed a PM with two muscular heads that fused to a common tendon, which corresponds to Olewnik et al [10] "bifurcated PM". Futa et al [3] observed another morphological variant similar to Smedra et al [14].…”
Section: Discussionmentioning
confidence: 96%
“…During a forensic autopsy, Smedra et al [14] observed a PM with two muscular heads that fused to a common tendon, which corresponds to Olewnik et al [10] "bifurcated PM". Futa et al [3] observed another morphological variant similar to Smedra et al [14]. Contrariwise, Kurtys, and coauthors [8] and Heo et al…”
Section: Discussionmentioning
confidence: 96%
“…There have been numerous reports detailing the anatomic variations of the plantaris muscle, including differences in its origin and insertion points [ [5] , [6] , [7] , [9] , [10] , [11] ]. However, the identification of an accessory plantaris with a separate muscle belly is a rare occurrence [ 5 , 9 , 12 , 13 ]. In a study that used MRI, Herzog et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that used MRI, Herzog et al. found that an accessory plantaris was present in 6.3% of their study population [ 9 , [12] , [13] , [14] ]. Other instances of accessory plantaris have been identified in cadaveric studies, and there have been discussions regarding the potential implications of such variations for surgical procedures involving the popliteal fossa [ 9 , [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation